Design of a Medium Scale Ambient PM2.5 Cleaning System - Sheng-Chieh Chen; Qingfeng Cao; Thomas H. Kuehn; Charles Lo; Manoranjan Sahu; Yelia S. Mayya; David Y. H. Pui (Aerosol and Air Quality Research)
Abstract High concentrations of ambient particulate matter (PM) have caused millions of premature deaths annually worldwide. The source control strategy was normally implemented to bring the PM pollution down to meet the standards. However, it took more than 50 years for UK and US. As PM pollution is hurting people’s health on daily basis in many countries, a fast and inexpensive control technology should be developed to remedy the slow pace of source control. It should be applied in highly polluted areas, e.g., cities and industrial parks, where people are spending a considerable time outdoors. In this study, a medium-scale filter-based blower-driven cleaning system was designed based on a computational fluid dynamic (CFD) simulation and experiments. We found the system with a dimension of 20 m (L) × 20 m (W) × 23 m (H) using 40 sets of 40-HP blowers can output ~1000 m3 s−1 (CMS) of cleaned air. In PM removal, the design of the system, including the filter specifications, filter bank arrangement, and filter quantity, is crucial which results in the PM filtration efficiency, filter service life, and energy consumption. The clean air delivery rate (CADR), the product of the system flow rate (1000 CMS) and filtration efficiency (> 80%), is expected to be more than 800 CMS or ~70,000,000 m3 day−1 (CMD). The experiments showed that the filter service life is expected to be 2 and 6 months for the prefilter and final filter, respectively, under total suspended particulate and PM2.5 concentrations of 600 and 300 (µg m−3, respectively. The CFD simulations showed the area of the effective PM2.5 reduction zone (> 50% PM2.5 concentration reduction) is as large as ~300 m in diameter by this system. The CFD model also shows deploying 400 cleaning systems with 1 km apart, the PM2.5 reduced zone can cover an area of 400 km2.